PENGARUH PROFITABILITAS, STRUKTUR AKTIVA, KEBIJAKAN DEVIDEN DAN UKURAN PERUSAHAAN PADA STRUKTUR MODAL (STUDI KASUS PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR PERUSAHAAN CONSUMER GOODS YANG TERDAFTAR DI BEI TAHUN 2018-2020) - Sumardi Ilham; Rokhmawati Andewi; Haryetti Haryetti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine the effects of Profitability, Asset Structure, DividendPolicy and Company Size on Capital Structure (Case study of ManufacturingCompanies in the Consumer Good sub-sector on the IDX 2018-2020). Thepopulation in this study includes all manufacturing companies in the consumergoods sub-sector, totaling 58. Companies, Secondary data obtained or collectedand confirmed by studies previous studies or published by various other agencies,to test the hypothesis in this study is to use multple linear regression analysis withthe help of the SPSS program. Selected sampling technique in the method ofdocumentation with ( 34 sub-sector manufacturing companies consumer goodslisted on the IDX ). The result of this study indicate that : 1) there is a positive andsignificant influence of profitability on the capital structure of consumer goodscompanies, 2) there is a positive and significant effect of asset structure on thecapital structure of consumer goods companies, 3) there is a positive andinsignificand influence of dividend policy on the capital structure ofconsumergoods companies,4) there is a positive and significant effect of companysize on the capital structure of consumer goods companies. Keywords : Profitability, Asset Structure, Dividend Policy, Company Size, andCapital Structure.